The Influence of Muscular Fatigue on Human Multi-Joint Movement: Determinants of Sit-to-Stand Capacity with Aging - Bryanton, Megan (Université d'Ottawa / University of Ottawa, 2016)
The sit-to-stand (STS) is a multi-articular movement of daily living that requires significantly higher knee extensor (KE) efforts compared to ankle and hip musculature, which approach near maximal levels in older adults populations. As well, fatigue may develop more readily with repetitive actions. Consequently, it is understandable how KE strength reserves have been previously correlated with both functional independence and STS strategy characteristics in older persons, and why STS capacity is a significant predictor of disability. However, it is still unclear why compensatory movement strategies manifest when rising from a seated position, and how this may be influenced by aging. The purpose of this thesis compilation was to evaluate alterations in muscular contributions at the ankle, knee, and hip, in relation to STS performance strategies in young and older adults either: a) with repetitive multi-joint STS exercise or b) before and after isolated fatigue of KE musculature. Results showed that aging caused a redistribution of joint torques when ascending from a seated position, and was associated with significantly higher quadriceps muscular efforts in older persons in comparison to their younger counterparts. In contrast, young and older adults exhibited similar compensatory movement and loading strategies during repetitive STS exercise, which appeared to be limited by the ability to sustain KE force output. In turn, lower KE strength reserves of older persons were responsible for their disproportionately higher quadriceps efforts and reduced STS capacities. Young and older persons also appeared to employ motor strategies to compensate for reduced KE force output via increased contribution of the biarticular rectus femoris within the quadriceps KE synergy, as well as through increases in the initially less active ankle plantar flexor and hip extensor musculature. Older adults may benefit from strengthening of thigh extensor musculature to maintain or improve their strength reserves to promote independent living.
Keywords: Sit-to-Stand; Aging; Fatigue; Knee extensors